The diet of Great Tit Parus major nestlings in a Mediterranean Iberian forest: the important role of spiders - Pagani–Núñez, E.; Ruiz, Í.; Quesada, J.; Negro, J. J.; Senar, J. C. (Animal Biodiversity and Conservation, 2011)
The diet of the Great Tit Parus major when rearing chicks has been described in many studies. However, data from the Mediterranean area is scarce. Here we describe the diet of nestlings in a population of Great Tits in a Mediterranean forest in Barcelona (north–east Spain) during two breeding seasons using two methods: neck–collars and video recording. The main prey were caterpillars (44% from neck–collar data and 62% from video–recorded data), but in our latitudes spiders also seemed to be an important food resource (24% from neck–collar data and 42% from video–recorded data). We did not find any significant differences in the quantity of spiders collected by parents in relation to stage of chick development, main vegetation surrounding nest boxes, size of the brood, or year. Our results stress the importance of spiders as a food source in Mediterranean habitats.